Regulation of Schwann cell proliferation and migration via miR-195-5p-induced Crebl2 downregulation upon peripheral nerve damage - Li, Shiying; Wu, Wenshuang; Zhang, Jing; Chen, Yu; Wu, Yumeng; Wang, Xinghui (Frontiers in Cellular Neuroscience, 2023)
Schwann cells acquire a repair phenotype upon peripheral nerve injury (PNI), generating an optimal microenvironment that drives nerve repair. Multiple microRNAs (miRNAs) show differential expression in the damaged peripheral nerve, with critical regulatory functions in Schwann cell features. This study examined the time-dependent expression of miR-195-5p following PNI and demonstrated a marked dysregulation of miR-195-5p in the damaged sciatic nerve. CCK-8 and EdU assays showed high miR-195-5p levels decreased viability and proliferation in Schwann cells, while suppressed miR-195-5p exerted reverse effects. Next, elevated miR-195-5p promoted Schwann cell migration determined by the Transwell and wound healing assays. In vivo injection of miR-195-5p agomir into rat sciatic nerves promote axon elongation after peripheral nerve injury by affecting Schwann cell distribution and myelin preservation. Bioinformatic assessment further revealed potential regulators and effectors for miR-195-5p, which were utilized to build a miR-195-5p centered competing endogenous RNA network. Furthermore, miR-195-5p directly targeted cAMP response element binding protein-like 2 (Crebl2) mRNA via its 3’-untranslated region (3’-UTR) and downregulated Crebl2. Mechanistically, miR-195-5p modulated Schwann cell functions by repressing Crebl2. Jointly, the above findings suggested a vital role for miR-195-5p/Crebl2 in the regulation of Schwann cell phenotype after sciatic nerve damage, which may contribute to peripheral nerve regeneration.